KOMPENSASI, KERJASAMA TIM DAN KREATIVITAS BERDAMPAK TERHADAP KINERJA KARYAWAN (STUDI KASUS DI MCDONALD’S AREA SOLO RAYA): Pengaruh Citra Merek, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Smartphone Xiaomi Di Kota Surakarta - Yofhi Septian Panglipurningrum; Andika Eka Prasetya (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study aims to examine compensation, teamwork and creativity on employee performance. Research conducted at McDonald's fast food company solo area in 2019. Samples taken in this study were 40 employees. The analysis technique in this study consisted of validity and reliability tests, classic assumption tests, multiple linear tests, t tests, F tests and R2 tests (coefficient of determination). The results of multiple linear regression tests can be seen that compensation, teamwork and creativity have a positive effect on the performance of McDonald’s Solo area employees. T test results can be seen that compensation, teamwork and creativity significantly influence the performance of McDonald's employees Solo Area. F test results can be seen that compensation, teamwork and creativity significantly influence the performance of McDonald's employees Solo Area. R2 test results (coefficient of determination) obtained Adjusted R2 value of 0.246 which means that the variable influence of compensation, teamwork and creativity on the performance of McDonald's employees Solo Area can be explained by 24.6%. While the remaining 75.4% is explained by other variables not included in the regression model, for example leadership, work environment and incentives.